Zastosowanie funkcji produkcji w rachunku efektywności ekonomicznej gospodarstw chłopskich - Zeliaś, Aleksander (Wydział Prawa i Administracji UAM, 1966)
The aim of this study is to examine the quantitative relations existing between the agricultural production and the level of factors, which determine that production. The fullfilment of this goal is brought about by determining the function of agricultural production. The statistical data which were worked upon in this paper come from private farms which are keeping — for the benefit of the Institute of Agricultural Economy — special accounts, The studies concentrate on material and data characteristic for agriculture in two regions: the mid-western and eastern ones, for the years of 1960/61—1962/63 — for the sake of eliminating the influence of climate and haphazard chance. As a production function the author used the extended and modified version of Cobb - Douglas. The mathematical form of function in this dissertation has a stochastical character, what in turn means, that besides independent variables a chance element has been introduced. After a preliminary examination of the many possible production factors which could be taken into consideration the author has selected the following: land, work, live stock, machines and tools, mineral fertilizers. The extended form of Cobb-Douglas function has already been used in research on agricultural production of individual farms. In the paper the author is introducing his own innovations concerning the argumentation and attempt of economical interpretation of negative values of some coefficients of elasticity, which explain the reaction of agricultural production to individual cost and is putting forward his own ideas of defining the average error in the estimate of a chance element. The equations of production, which have been established on a regional scale can be useful in initiating a rational agricultural policy and can serve as a basis for making proper financial allocations in agriculture.